Taxonomic status of three controversial species of Cephalanthera (Orchidaceae) from Korea based on morphological and molecular data - Shin, Hye Woo; Lee, Chang Shook; Choi, Sun A; Eum, Sang Mi; Lee, Nam Sook (Phytotaxa, 2019)
The taxonomic status of three of the seven Cephalanthera species in Korea is controversial: C. erecta var. oblanceolata, C. subaphylla, and C. shizuoi. To clarify their taxonomic status, we used molecular data of ITS of nuclear DNA, and three regions of chloroplast DNA (matK, rpl16 and trnL-F), in addition to morphological characters. We analyzed 82 accessions collected from 26 sites including the other four taxa: C. erecta, C. falcata, C. longibractea, and C. longifolia. The analysis of ITS, matK, rpl16 and trnL-F data showed that Cephalanthera erecta var. oblanceolata should be treated as a synonym of C. erecta. Molecular data supported that C. subaphylla is an independent species rather than a variety or forma of C. erecta. Cephalanthera shizuoi was currently treated as a synonym of C. erecta or C. longifolia based on morphology and the molecular data supported that C. shizuoi should not be recognized as distinct species; but C. shizuoi should be a synonym of C. longifolia, not a synonym of C. erecta.